2022
DOI: 10.22541/au.164914936.65736086/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The fluid definition of the ‘waters of the United States’: Non-uniform effects of regulation on US wetland protections

Abstract: Recent revisions to the definition of the “waters of the United States” (WOTUS) have considerably altered how wetlands are federally regulated under the Clean Water Act. The two most recent modifications to WOTUS, the Clean Water Rule (CWR) and the Navigable Waters Protection Rule (NWPR), represent two opposing approaches to the federal wetland policy. Despite their implementation, the impacts of these rules on the regulation of wetlands have as of yet been poorly characterized at broad spatial scales. Using N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These federally protected, or federally jurisdictional, waters are defined as "waters of the United States" (WOTUS) by the US Environmental Protection Agency (EPA) and US Army Corps of Engineers (USACE). WOTUS generally includes large "navigable" water bodies and the streams and wetlands connected to them, but the specific definition of WOTUS and what "connected" means has shifted over the past 20 years and has had significant impacts on which waterbodies, streams, and wetlands are protected by the federal government (2,3).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…These federally protected, or federally jurisdictional, waters are defined as "waters of the United States" (WOTUS) by the US Environmental Protection Agency (EPA) and US Army Corps of Engineers (USACE). WOTUS generally includes large "navigable" water bodies and the streams and wetlands connected to them, but the specific definition of WOTUS and what "connected" means has shifted over the past 20 years and has had significant impacts on which waterbodies, streams, and wetlands are protected by the federal government (2,3).…”
Section: Main Textmentioning
confidence: 99%
“…Given the importance of wetland ecosystems and their myriad beneficial downstream impacts (12), there is a critical need to capture the full range of potential impacts of the Supreme Court's decision. While federal jurisdictional status of waters and wetlands can only be determined by the EPA and USACE, prior studies have demonstrated the utility of estimating federal jurisdictional status based on physical characteristics that align with definitions of WOTUS (3,13,14) This study estimates the federal jurisdictional status of non-tidal wetlands in the conterminous US using a range of potential interpretations of the Supreme Court's Sackett v. EPA majority opinion. The potential interpretations presented here use different wetland flooding frequency thresholds as a proxy for a "continuous surface connection", so wetlands that are "drier" than a given flooding frequency threshold cannot be estimated jurisdictional.…”
Section: Main Textmentioning
confidence: 99%
“…Based on the specific NFW types, relevant studies have been found across all seven continents, but the studies are predominantly located in North America (between 39% and 96%, for the nine main types; figure 1(b)). This result is presumably due to the origination of 'NFW' terminology, and the further development of legislative/regulatory and management/ funding policies around NFWs in the U.S. (Sullivan et al 2020, Wade et al 2022. Apart from potholes, in which the dominant subtype of prairie potholes is endemic to North America, literature from Asia and Europe have a combined share of pond, marsh, and constructed wetland research, reaching 33%-53%, each close to or higher than that of North America.…”
Section: Nfws Have Been Widely Studied With Strong North America Infl...mentioning
confidence: 99%
“…Not surprisingly, other countries, such as U.S., have different and often conflicting policies between federal and state governments-The former has once enforced rules that put NFWs at risk but now more generally promote conservation, whereas the latter have often enacted additional, protective regulations (e.g. Florida in particular) (Creed et al 2017, Sullivan et al 2019, Wade et al 2022. Additionally, laws and regulations that implement indirect protection have been emerging in a few countries over the past two decades.…”
Section: Legislation/regulationmentioning
confidence: 99%